A Compact High-Gain Metasurface Antenna for 5G Applications - Sathwik K.; Swain B.R.; Bhattacharya S.; Samantaray D. (My University, 2025)
This paper provides valuable insights into the design, development, and implementation of a 5G metasurface antenna (MSA). The MSA is assembled with a simple microstrip patch antenna that achieves the realized gain of 4.8dBi using substrate of Rogers RT Duroid 5880 (Lossy) at a frequency of 25.9 GHz. The two-layer 4 × 4 order metasurface (MS) has enhanced the gain of the antenna to 9.31dBi. The dimensions of the proposed antenna are 0.52 λ0 × 0.52 λ0 × 0.51 λ0 where λ0 is the free space wavelength at 25.9GHz. The overall 4 × 4 MSA also provides the maximum efficiency of 86 % at 25.9GHz. The proposed antenna's outstanding performance offer a promising avenue for future 5G deployments, catering to the demands of diverse applications in the era of next-generation wireless networks. © 2023 IEEE.